Use of soybean gum as an emulsifier in diets for commercial laying hens - Pedro Souza, Rosemary Pereira de [UNESP]; Laurentiz, Antonio Carlos de [UNESP]; Faria, Glaucia Amorim [UNESP]; Filardi, Rosemeire da Silva [UNESP]; Mello, Erica do Santos [UNESP] (Empresa Brasil Pesq Agropec, 2019)
The objective of this work was to evaluate the influence of the inclusion of soybean (Glycine max) gum in the diet of laying hens on egg production, egg external and internal quality, and economic viability, as well as of temperature and storage time on the oxidative stability of eggs. One hundred and eighty 40-week-old Lolunann-LSL layers were fed 0, 1, 2, 3, 4, and 5% soybean gum in the diet. In the economic analysis, the average productive performance of the layers and the cost of feed were considered. In order to evaluate oxidative stability, eggs were stored at room temperature (similar to 30 degrees C) or refrigerated (5 degrees C) for 0, 7, and 21 days. The inclusion of soybean gum in the diet increased feed intake and also egg production, average weight, and mass. Soybean gum improved external and internal egg quality parameters, but reduced the Haugh unit. Oxidative stability was higher in eggs from hens fed 4% gum, at 5 degrees C, for 21 days; however, the largest economic return was with 1% gum. The inclusion of soybean gum promotes improvements in the production, external and internal quality, and oxidative stability of eggs from commercial laying hens.
Keywords: egg quality; lecithin; oxidative stability; performance; phosphatidylcholine